Valence shell electronically excited states of imidazole and 1-methylimidazole - Holland, D. M. P.; Shaw, D. A.; Townsend, D.; Powis, I. (Molecular physics, 2023)
The absolute photoabsorption cross section of imidazole, and that of 1-methylimidazole, have been measured from threshold up to 10.8 eV using synchrotron radiation. For each molecule, the absorption spectrum exhibits several broad bands due to transitions into excited valence states and some sharp structure associated with Rydberg states. Assignments have been proposed for some of the observed absorption bands using calculated transition energies and oscillator strengths. Quantum defect analyses have also helped guide these assignments. Natural transition orbital plots indicate that many of the electronically excited states have a mixed Rydberg/valence character. This mixing leads to irregularities in both the transition energies and the relative intensities of the absorption bands ascribed to Rydberg states. The vibrational progressions belonging to some of the Rydberg states have been interpreted using simulations of the corresponding cation's vibrational structure obtained within the Franck-Condon model employing harmonic frequencies and normal modes.